2010
DOI: 10.1590/s0104-12902010000400012
|View full text |Cite
|
Sign up to set email alerts
|

Análise da atenção básica em cinco municípios da amazônia ocidental, com ênfase no Programa Saúde da Família

Abstract: ResumoO objetivo deste artigo é analisar o processo de gestão da atenção básica, aí incluído o Programa de Saúde da Família (PSF), em cinco municípios da Amazônia Ocidental. A descentralização, entendida como meio de aprimoramento da gestão local, também foi investigada. Trata-se de um estudo qualitativo, que explorou o plano político-institucional dos sistemas de saúde dos municípios, através das dimensões projeto de governo, capacidade de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
11

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 9 publications
0
10
0
11
Order By: Relevance
“…Apesar de os estudos não trazerem dados sobre o grau de capacitação dos profissionais nestas áreas de interesse, a necessidade se dá pela tendência dos serviços de saúde a aderir à informatização do serviço, a partir da implantação de sistemas informatizados de regulação, prontuários eletrônicos, e fóruns digitais de discussão, o que demanda dos gestores locais cada vez mais o desenvolvimento de habilidades sobre a manipulação destas ferramentas 9,17,19 .…”
Section: Atuação E Formaçãounclassified
See 2 more Smart Citations
“…Apesar de os estudos não trazerem dados sobre o grau de capacitação dos profissionais nestas áreas de interesse, a necessidade se dá pela tendência dos serviços de saúde a aderir à informatização do serviço, a partir da implantação de sistemas informatizados de regulação, prontuários eletrônicos, e fóruns digitais de discussão, o que demanda dos gestores locais cada vez mais o desenvolvimento de habilidades sobre a manipulação destas ferramentas 9,17,19 .…”
Section: Atuação E Formaçãounclassified
“…Dessa forma, a literatura revela que os gestores locais se sentem satisfeitos e motivados no seu contexto de trabalho 17 .…”
Section: Atuação E Formaçãounclassified
See 1 more Smart Citation
“…However, as regard to the planning construction, the interviewees identified a low utilization on the existing documents to base their choices of action. This reality is becoming worse by the result on the analysis of the management processes on primary care in the Amazon according to Vieira et al 16 This study 16 recognized the difficulties of the cities to identify priorities, lack of financial capacity and support base for policy to put into practice what was already planned.…”
Section: Discussionmentioning
confidence: 99%
“…This form of the State to act had already been evidenced in a study with five towns in the Amazon State that sought to analyze the basic care and observed the dispute of the execution of actions at this level of care among the Cities and State. 16 The State centrality is adding weaknesses in the collective negotiations of CIR, which brings impacts to the constitution of RAS and in the form of how it consolidates to APS and RUE. The limitations of CIR create an action model of bureaucracy at the detriment of setting up as a collective construction space.…”
Section: S245mentioning
confidence: 99%